HYDRODYNAMIC AND THERMAL TWO DIMENSIONAL BOUNDARY LAYERS DEVELOPMENT BETWEEN ROTATING TURBINE BLADES (Journal of Engineering, 2010)
The hydrodynamic and thermal boundary layers have great effect on the fluid flow and heat transfer between rotating turbine blade. In the present work, the flow and heat transfer is analyzed numerically by solving two dimensional incompressible boundary layer equations. A ( k – ε ) turbulence modeling is used to obtain the eddy viscosity. The finite volume method is introduced to carryout all computational solution with staggered grid arrangement. Due to complex physical domain the original coordinate system is transferred to non orthogonal coordinate system. The calculation of present work done for rotating two dimensional turbine cascade with different rotating speeds (1500 rad/s, 1800 rad/s, 1900 rad/s), and for different Reynolds number (5000, 10000, 100000), in subsonic flow (M